Child Education in the Perspective of Sundanese Local Wisdom and Islamic Teachings - Siti Nuroh; Ari Nugraha; M. Sulhan; Ilham Solihin (Journal of Public Policy Analys, 2025)
In the millennial era, Indonesian culture has emerged as the result of a long process of acculturation involving various external influences, including Hinduism, Buddhism, Islam, and Christianity. This acculturation process has indirectly shaped and influenced the values, norms, social systems, and customary laws of local cultures. As the religion embraced by the majority of Indonesians, Islam has significantly contributed to shaping moral and educational systems, particularly in child-rearing practices. This article aims to analyze child education from the perspective of Sundanese local wisdom and its relevance to Islamic teachings. This study employs a qualitative approach using a phenomenological method to explore the essential meanings behind the experiences and realities of the Sundanese community in educating their children. The findings are expected to provide a deeper understanding of the integration of Islamic values with local cultural traditions in shaping children's character from an early age.